Tecnologia de aplicação aérea de fungicidas na cultura do arroz irrigado - Silva, Tânia Maria Bayer da (2009)
The objectives of the study were: a) evaluate the equipment and aerial application rates to maximizing the coverage and penetration of fungicides drops in the canopy leaf through Water-sensitive paper and chromatography b) measure the spectra of droplets generated by hydraulic nozzles, nozzles electrostatic and rotating atomisers disk c) evaluate the yield components: seed yield and ingenuity income d) evaluate the control of Cercospora oryzae in accordance with the devices tested. For the deposition of drops in three tiers with Water-sensitive papers review, the hydraulic nozzle equipment with 30 L.ha-1 had higher deposition in the upper third and medium. For the bottom third, the rotary atomizer disks in the rate of 15 L.ha-1 had higher penetration. With chromatography, the largest amount of product in the lower canopy was achieved through the electrostatic equipment with 10 L.ha-1. For the control of Cercospora oryzae the data were not consistent, because the treatments did not differ from the witness. For weight and grain yield there was no difference among treatments. For ingenuity income, the weight of grain was obtained using the hydraulic equipment Nozzle 20L.ha-1. The penetration and density were evaluated in relation to rates and equipment through contrasts. Most treatments showed differences between the equipment and rates.